Single ultrasound-guided thoracic paravertebral block with a large volume of anesthetic for microwave ablation of lung tumors - Ni, Yong; Zhong, Yulong; Zhang, Yue; Tao, Yifei; Pan, Jiang; Zhao, Yiming; Zhang, Zhicheng; Jin, Yong (Frontiers in Oncology, 2022)
Abstract Objective: To compare single ultrasound-guided thoracic paravertebral block (TPVB) using a large volume of anesthetic with local anesthesia (LA) in computed tomography (CT)-guided pulmonary microwave ablation. Subjects and methods: Eighty patients who underwent CT-guided microwave ablation of pulmonary tumors were randomly divided into the TPVB group and the LA group. Patients of the TPVB group were anesthetized with a single injection of a large volume (40 mL) of 0.375% ropivacaine injection at T4, and those of the LA group with local infiltration by the surgeon at the puncture site, and emergency rescue with propofol injection was administered when the patient could not tolerate pain in either group. The following variables were recorded in both groups: general conditions, volume of propofol injection for emergency rescue during ablation, Visual Analog Scale (VAS) scores during ablation and at 0, 2, 12, and 24 h after ablation, the need to use analgesics for rescue within 24 h after ablation, number of ablations, number of punctures performed by the surgeon, patient’s movements during puncturing, and puncturing-associated complications. Results: Compared with TPVB group, the amount of emergency use of propofol injection was significantly more in LA group (P<0.05). There were no significant differences in the VAS scores recorded intraoperatively and at 0, 2, 12, and 24 h after ablation between the two groups (P>0.05). There was a significant difference in the patient’s movements upon puncturing between the two groups (P<0.05), but there were no significant differences in the numbers of punctures and ablations between the two groups (P>0.05).The number of patients using analgesics within 24 hours after operation was also more in the LA group compared with the TPVB group , and the difference between the two groups was statistically significant (P<0.05). Conclusion: Single ultrasound-guided TPVB with a large volume of anesthetic offers effective analgesia for microwave ablation of lung tumors, helping the patient cooperate with the operating surgeon to reduce injury from multiple lung punctures. Further studies are recommended to validate these findings.